Fresno County Bar Associations' 105th Annual Bar Banquet - Watkins, Howard::::::::: (1987)
Fresno County's third County Counsel Max Robinson and Fresno County's first County Counsel Robert Wash Floyd Viau was the second Fresno County Counsel